2019
DOI: 10.31557/apjcp.2019.20.11.3331
|View full text |Cite
|
Sign up to set email alerts
|

Association between C1236T Genetic Variant of ABCB1 Gene and Molecular Response to Imatinib in Indonesian Chronic Myeloid Patients

Abstract: Upon treatment with imatinib, most patients restore normal hematopoiesis (Hochhaus et al., 2018). The long-term efficacy and safety imatinib in CML patients in the chronic phase have been established in IRIS Study (Hehlmann et al., 2017; Hochhaus et al., 2017; Hochhaus et al., 2018). After almost 11 years of follow-up, overall survival at ten years in imatinib-treated patients was 83.3% with no notable toxic effects (Hochhaus et al., 2017). Nonetheless, about 20-30 % of CML patients failed

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 26 publications
0
6
0
Order By: Relevance
“…However, ABCB1 rs1128503 (G), a minor allele in other SEA populations, was found to be a major allele among Filipinos. Previously, rs1128503 (G) was documented as a major allele among Chinese and Singaporean populations; however, rs1128503 (G) was found to be a minor allele in the Indonesian population 15 , 16 . rs1128503, rs2032582, and rs1045642 are the most common SNPs in the coding region of ABCB1 ; moreover, these SNPs are in strong LD 17 .…”
mentioning
confidence: 93%
“…However, ABCB1 rs1128503 (G), a minor allele in other SEA populations, was found to be a major allele among Filipinos. Previously, rs1128503 (G) was documented as a major allele among Chinese and Singaporean populations; however, rs1128503 (G) was found to be a minor allele in the Indonesian population 15 , 16 . rs1128503, rs2032582, and rs1045642 are the most common SNPs in the coding region of ABCB1 ; moreover, these SNPs are in strong LD 17 .…”
mentioning
confidence: 93%
“…Our results is also in accordance with the findings of Au et al [5] , Dulucq et al [18] , and Deenik et al [22] who reported that the patients with 1236CC genotype were associated with IM resistance, and those with 1236TT genotype showed higher probability to achieve IM response. In contrast, in several studies, no association was found between 1236CT and 3435CT genotypes and IM response [13,23,24] . Regarding the c.3435 CC genotype, Lardo et al [25] found the association of this genotype with the complete molecular response, while Ni et al [26] SNP/ gen. indicated the association of c.3435TT with the increased risk of IM resistance.…”
Section: Discussionmentioning
confidence: 76%
“…Our results is also in accordance with the findings of Au et al [ 5 ] , Dulucq et al [ 18 ] , and Deenik et al [ 22 ] who reported that the patients with 1236CC genotype were associated with IM resistance, and those with 1236TT genotype showed higher probability to achieve IM response. In contrast, in several studies, no association was found between 1236CT and 3435CT genotypes and IM response [ 13 , 23 , 24 ] .…”
Section: Discussionmentioning
confidence: 81%
“…Some studies have shown that MDR1 gene-related SNPs polymorphism may affect the Area Under Curve (AUC) or clearance rate of docetaxel [18,19]. At present, it has been found that there exits more than 50 SNPs in MDR1 gene, of which exon 12 (C1236T), 21 (G2677T/A) and 26 (C3435T) have high mutation frequency [20][21][22][23]. Liu et al found that breast cancer patients with T allele at C3435T locus had better chemotherapeutic efficacy than patients with C allele, but no significant difference was found in C1236T and G2677T/A polymorphism [24].…”
Section: Discussionmentioning
confidence: 99%